Giant nonfunctioning adrenal tumors: two case reports and review of the literature - George, Chatzoulis (J Med Case Rep, 2018)
BACKGROUND: There are an estimated 1–2 cases per million per year of adrenocortical carcinoma in the USA. It represents a rare and aggressive malignancy; it is the second most aggressive endocrine malignant disease after anaplastic thyroid carcinoma. Non-secretory adrenal masses are diagnosed late due to a mass effect or metastatic disease or found incidentally (adrenal incidentalomas). CASE PRESENTATION: The first case report describes a 39-year-old Greek woman who presented to our department with complaints of repeated symptoms of flatulence and epigastric discomfort over a few months. The second case report is about a 67-year-old Greek woman who presented to our department after being evaluated for fatigue, mass effect, and epigastric discomfort. Both of them were diagnosed as having a nonfunctioning adrenocortical carcinoma and underwent open adrenalectomy. CONCLUSIONS: Approximately 60% of patients with adrenocortical carcinoma present with symptoms and signs of hormonal secretion. Our cases’ adrenocortical carcinomas were not functional. Hormone secretion is not a discriminating feature between benign and malignant adrenocortical masses. The silent clinical nature of nonfunctioning adrenocortical carcinoma results in late diagnosis, while the majority of patients present with locally advanced and/or metastatic disease. Adrenocortical carcinoma is a rare endocrine tumor with a poor prognosis that can be diagnostically challenging and demands high clinical suspicion. The work-up for adrenal masses must include determination of whether the mass is functioning or nonfunctioning and whether it is benign or malignant.